„Mozart”, Węgry i Watykan 1962–1964. Akta wywiadu jako źródło historyczne - Bottoni, Stefano (Pamięć i Sprawiedliwość, 2014)
The object of this study is an extensive dossier produced between the years 1962 and 1965 by the Hungarian intelligence services on the German-born journalist of Gottfried Kusen, employed at the Vatican Radio since 1947 and resident in Italy since the early 1920s. Kusen, which was assigned by the officers operating in the residentura of Rome the codename of “Mozart”, is a person of extreme interest for those studying the early Vatican Ostpolitik, because he had spent his whole life in the “gray zone” where networks of intelligence and diplomatic contacts interact. A past qualified of the Italian fascist political police int he the second half of the 1930s, Kusen became the Abwehr from 1943 to 1945, then was linked to the British Intelligence Service in the early post-war years, and finally was finally employed by the Vatican Radio in close contact with the West German embassy in Rome. In the early 1960s, after the convening of the Second Vatican Council, Hun- gary, together with Poland was given by the Warsaw Pact the task of enhancing the disclosure of information on the Italian territory. People like Kusen – well introduced in Vatican circles and Italian politics – became necessary to enable the regime of János Kádár, looking for that compromise with the Holy See which was signed on September 15, 1964 to weaken the internal resistance of the Catholic world. The relationship with “Mozart”, which never became an agent and was in fact “abandoned” in 1965, ended in a defeat for the Hungarian espionage as the senior journalist, an expert on the psychological mechanisms and techniques of espionage, distributed to a large number of officers of espionage in the countries of the Warsaw Pact news and views representing the official view of the Vatican State Secretary. Presenting himself as a “socialist”, close to the ideological positions of the Soviet bloc countries, Kusen could intercept during the early stages of Ostpolitik themes and accents for a possible dialogue. The article traces the transactions which occurred between “Mozart” and the Hungarian intelligence directorate between 1962 and 1965. This relationshop was of particular importance since information coming from “Mozart” revealed in many cases really insightful, and helped the Hungarian communist regime to better understand the changing Eastern policy of the Vatican.